Soil copper and manganese availability to wheat (Triticum aestivum) as affected by long-term fertilization in an Inceptisol - DAS, ANIT; MEENA, MAHESH C; DATTA, S P; DWIVEDI, B S; DEY, ABIR (The Indian Journal of Agricultural Sciences, 2022)
Copper (Cu) and manganese (Mn) are two most important micronutrients, essential to living organisms through their involvement in different enzymes and other biologically active molecules. An experiment was conducted at the research farm of ICAR-Indian Agricultural Research Institute, New Delhi to investigate the impact of various fertilizers and manurial treatments on DTPA-extractable Cu and Mn in soil and their concentration in grain and straw of wheat (Triticum aestivum L.) after 46 years of continuous cropping. The soil and plants samples were collected at wheat harvest during April, 2018 and April, 2019 following fertilizers and manurial treatments: control, N alone, NP, NPK, 150% NPK, NPK+Zn and NPK+FYM. Results revealed that DTPA-extractable Cu did not show any significant variation among the various treatments except control but DTPA-Mn was highest under FYM treated plot. In addition, nutrient management options such as 150% NPK, NPK+FYM and NPK+Zn were equally effective in enhancing the yield of wheat. The concentration of Cu and Mn in grain varied from 5.25–7.63 and 28.5–36.4 mg/kg, respectively under different nutrient management options. Highest uptake of Cu and Mn was obtained under NPK+FYM treatment while control showed the lowest, indicating importance of organic manures for improving the nutritional quality of food grains. Transfer coefficient (indicating transfer nutrients from vegetative tissue to grain) of Cu did not change by fertilization and manuring to a significant level whereas balance and integrated use of fertilizers and manure significantly increased the transfer of Mn from straw to grains.